Publishing Research at the College of The Bahamas - Ballance, Virginia C. (International Journal of Bahamian Studies, 2015)
The College of The Bahamas has published 20 volumes of a research journal since 1980. The journal has had a stop-and-start history, undergone three name changes, and in 2008 made a major move from a print to an online environment. This overview of publishing a research journal at the College of The Bahamas traces its history and evolution through the years from a print journal to an open access electronic journal and to the International Journal of Bahamian Studies.